OHP-004 Prescription of oral anti-diabetic agents recently marketed in a health area. (24th February 2014) - Arribas-Díaz, B; Selvi-Sabater, P; Bosó-Ribelles, A; Sánchez-Martinez, I; García-Motos, C; Sánchez-Mulero, MC; Moregó-Soler, MA; Rizo-Cerdá, AM
Abstract : Background: The recently marketed anti-diabetic drugs are considered new options without great innovation. Purpose: To determine the prescription profile and economic impact of these drugs to make a more efficient use of resources. Materials and methods﻿: Retrospective study of six months of oral anti-diabetics (therapeutic subgroup A10B of the Anatomical, Therapeutic, Chemical classification system (ATC)) that were prescribed by the AdN application. One of the aims of the management contract in this health area is to limit prescription of recently marketed anti-diabetics. These drugs are included in the C group, setting them against cheaper agents such as metformin and sulfonylureas with which there is a great deal of experience. Results: During this study period 33, 458 packs of oral anti-diabetics were prescribed at a cost of 876, 382 €. The prescription of new oral agents accounted for 34.4% of packs at a cost of 739, 545€, 84.4% of total expenditure. Prescription rates are as follows: metformin/sitagliptin 41.9%, metformin/vildagliptin 33.4%, sitagliptin 11.1%, vildagliptin 4.5%, saxagliptin 3.3%, liraglutide 2.3% and linagliptin 2.3%. Over this period 12, 293 patients were treated with anti-diabetic drugs and 49.1% of them used one of these new drugs. Making an approximation of the average cost per patient treated, in the case of the new ones this is 122.4 €/patient compared to 71.3 euros in the classic ones. 96.5% of prescriptions came from primary care physicians and only 3% from cardiology and 2.0% from endocrinology and nutrition specialists. Conclusions: The new oral anti-diabetics represent a high rate of current treatment considering the number of patients as well as the health spending, so it is necessary to justify their use. Among the new anti-diabetics without a relevant contribution the most prescribed were metformin/sitagliptin and metformin/vildagliptin. Another important point is the high number of prescriptions from general practitioners versus specialists in this sample. No conflict of interest.